Pengaruh Biaya Promosi dan Biaya Kuliah Terhadap Jumlah Calon Mahasiswa Baru Menggunakan Regresi Linier Berganda - Yulia Utami; Desi Vinsensia (Pustaka Timur Publisher, 2022)
The purpose of this study was to show the effect of promotion costs and tuition fees on the number of prospective new students. The method used in this study is a quantitative method, with a research sample of the number of new students and promotion and tuition fees taken based on the data of the last 5 years. The analysis in this study uses multiple linear regression method where the equation Y = 178,890 – 21,730X1.+ 101,352X2 has been obtained. Fcount obtained is 1026,251 while Ftable is 19,00. Based on the comparison of Fcount and Ftable, H0 is rejected, so the conclusion obtained is that there is a significant influence between tuition fees and promotion costs on the number of new students on the STMIK Pelita Nusantara campus.